2014
DOI: 10.1017/s0950268814002040
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with recently acquired hepatitis C virus infection in people who inject drugs in England, Wales and Northern Ireland: new findings from an unlinked anonymous monitoring survey

Abstract: Monitoring infections and risk in people who inject drugs (PWID) is important for informing public health responses. In 2011, a novel hepatitis C antibody (anti-HCV) avidity-testing algorithm to identify samples compatible with recent primary infection was introduced into a national surveillance survey. PWID are recruited annually, through >60 needle-and-syringe programmes and prescribing services. Of the 980 individuals that could have been at risk of HCV infection, there were 20 (2%) samples that were compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…For hepatitis C, a previously described algorithm using antibody avidity testing was applied to the survey samples to identify probable recent hepatitis C infections, i.e. samples with weak antibody avidity < 40% in the presence of HCV RNA [24]. For anti-HBc, an in-house IgG class-specific antibody capture enzyme immunoassay (EIA) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For hepatitis C, a previously described algorithm using antibody avidity testing was applied to the survey samples to identify probable recent hepatitis C infections, i.e. samples with weak antibody avidity < 40% in the presence of HCV RNA [24]. For anti-HBc, an in-house IgG class-specific antibody capture enzyme immunoassay (EIA) was used.…”
Section: Methodsmentioning
confidence: 99%
“…A laboratory testing algorithm was applied to the samples collected in the survey to identify probable recent infections with HCV [24], i.e. those with weak anti-HCV avidity in the presence of HCV RNA.…”
Section: Health Harms and Mephedrone Injectingmentioning
confidence: 99%
“…The prevalence of HCV infections and the coverage of harm reduction interventions such as NSPs and OST varies across the UK, 16,20,39,44,70,73,[87][88][89][90] and although the coverage of OST has increased in the past 10 years, the level of high-coverage NSPs has remained relatively constant. 70 In this chapter, a HCV infection transmission and progression model, incorporating new evidence on intervention effectiveness, is used to assess the impact of current levels of OST and NSP on HCV infection prevalence, incidence and HCV-related morbidity among current and ex-injecting drug users in three UK settings, and the probable impact of scaling up NSP coverage.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of hospitalized IDUs in Switzerland, the three most common infections were, in order of frequency, skin and soft tissue infections, pneumonia and endocarditis (37.5%, 21.8% and 15.7%, respectively) (14). Investigations elsewhere have also indicated that skin and soft tissue infections are the most common types of bacterial infections among IDUs (15)(16)(17)(18)(19). In general, as shown previously and observed in our study, skin and soft tissue infections are the most common diseases identified in admitted IDUs; the prevalence of other common infections including pneumonia, bone and joint infections, and endocarditis varies between different studies.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Injection Drug Users often refrain from hospital admission and delay receiving proper care for as long as possible (19,29). An infection that could be easily treated with a proper combination of intravenous and oral antibiotics is only partially treated, thus markedly prolonging the course of the disease.…”
Section: Implications For Harm Reductionmentioning
confidence: 99%